Spotlight: questões da produção em Button Poetry - Rocha, Letícia Assis Michalczyk (Universidade Federal de São Carlos, 2023)
In this research, we analyze the production inside the Button Poetry channel on YouTube as a form of confrontation to patriarchal impositions throughout poetry. We have drawn a line of stereotypes imposed to women, using WOOLF (1929; 1942; 1989), DE BEAUVOIR (2016) and PLATH (2014; 2019) to contextualize the decision to investigate the idea of Manic Pixie Dream Girl (RABIN, 2007) with the performance of GATWOOD (2015) and, also, the conflicts related to mental health and generational trauma in women with the performance of BENAIM (2014) from the Button Poetry YouTube channel, a literary setting in digital environment. Aiming to investigate the materiality we have used the discursive-midiological line and Discourse Analysis, with Regis Debray and Dominique Maingueneau theories, yet, tracing a reflexion about literature and new media (ROCHA, 2016; 2019). While considering Button Poetry channel as a midium (DEBRAY, 2000) we have established an investigation of its functioning in the platform in which it is inserted, with the perspective of Organized Matter and Materialized Organization (DEBRAY, 2000) as well as analyzing slam poetry performances (PINTO, 2017) and what overflows the literary (GARRAMUÑO, 2014). From what has been exposed, we study two videos with performances of authorship of women in the youtube channel to notice the production related to gender in a digital environment.
Spotlight: women's authorship in Button Poetry
Keywords: Produção de mulheres; Women's authorship; Manic Pixie Dream Girl; Midium; Button Poetry; YouTube; Mídium; LINGUISTICA, LETRAS E ARTES::LETRAS::TEORIA LITERARIA